Two new species of Mallomonas (Chrysophyceae: Synurales): Mallomonas temonis and Mallomonas divida - Němcová, Yvonne; Kreidlová, Jana (Phytotaxa, 2013)
This paper describes two new species of Mallomonas. Mallomonas temonis was identified in the Table Mountain Plateau, South Africa; Mallomonas divida was identified in Aquitaine, France. The descriptions are based on silica-scale morphology studied by means of transmission and scanning electron microscopy. Mallomonas temonis belongs to the section Heterospinae. A scale is surrounded by a submarginal rib connected at lateral parts by a strong, more or less transversal rib. Mallomonas divida belongs to the section Torquatae. The shield of scales is covered by regularly arranged, delicate papillae and marked by one or several rows of more distinctive papillae.